Board Gender Diversity as a Conditional Governance Resource: Evidence from Environmental Innovation in China’s Low-Carbon Transition - Shanshan Yue; Farhanullah Khan; Khartic Rao Manokaran; Xue Lei (Heca Sentra Analitika, 2026)
As firms face increasing pressure to support the transition toward a low-carbon economy, corporate governance has emerged as a critical mechanism shaping environmental innovation. This study examines whether and under what conditions board gender diversity contributes to environmental innovation in China’s listed firms. Drawing on upper echelon theory and the resource-based view, we argue that gender-diverse boards enhance cognitive diversity and stakeholder orientation, thereby strengthening firms’ capacity to pursue sustainability-oriented innovation. Using panel data from Chinese A-share listed companies over the period 2014-2023, the results show that board gender diversity is positively associated with environmental innovation, measured by green patent output. However, this relationship is not uniform across institutional contexts. The positive effect is significantly stronger in non-state-owned enterprises than in state-owned enterprises, suggesting that organizational flexibility and market-oriented governance conditions influence whether diversity can be effectively translated into low-carbon outcomes. These findings contribute to the literature by demonstrating that board diversity operates as a conditional governance resource rather than a universally effective mechanism. The study also offers implications for policymakers and firms seeking to align governance reforms with low-carbon transition objectives in emerging economies.